Attitudes and perceptions of nurses regarding early communication intervention - Brenda Louw; Ingrid Weber (AOSIS, 1997)
Although nurses play a vital role during Early Communication Intervention with infants and toddlers 0-2 years, limited research has been conducted regarding this role. Opsomming Alhoewel verpleegkundiges 'n belangrike rol speel in Vroee Kommunikasie Intervensie met hoerisiko-babas en kleuters van 0-2jaar, is beperkte navorsing egter uitgevoer oor hierdie rol. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.